Pemidanaan terhadap Korban Psikotropika (Tinjauan Viktimologi dalam Penjatuhan Pidana terhadap Penyalahguna Psikotropika) - Vivi Ariyanti (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2015)
The misuse of psychotropic is classified as “crime without victim”. It isincluded as a norm deviation which does not cause a lose or danger to other people.In this case, the one who become victim is the doer himself. For the user, he has to get a protection in a for of rehabilitation. This rehabilitation is for recovery and it is regulated in pasal 41 UU No.5 Tahun 1997. In the misuse of psychotropic, criminalizing in a narrow point of view is to send the criminal to the prison. This treatment is not perfect for those who already in serious condition or those who need rehabilitation and medical watch-out, this criminalizing leads to worse effect.